A Comparative Study on The Influence of Physiological Factors and Genetics on Egg Quality in Arabic, Kedu Kup, and Pelung Chicken Breeds - Ahmad, Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aimed to determine the influence of genetic and physiological factors on egg quality in Arabic, Kedu Kup, Pelung chicken breeds, to compare the differences in egg quality between Arabic, Kedu Kup, and Pelung chicken breeds. A quantitative research technique was adopted in this study. Two hundred eggs were randomly gathered; one hundred came from a rural location and the other hundred came from a commercial source. SPSS software version 20.0 is used in this study’s data processing procedure. This study uses both ANOVA and multiple linear regression for data analysis. The study’s findings indicated that genetic and physiological variables significantly affect the quality of eggs in Arabic, Kedu Kup, and Pelung chicken breeds. Additionally, there are notable variations in the quality of eggs across these breeds. When choosing breeds for egg production, poultry producers are advised to take breed-specific characteristics into account.